2011
DOI: 10.1016/j.optmat.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Surface ablation of RbTiOPO4 by femtosecond laser

Abstract: We report here the results obtained in surface ablation of RbTiOPO 4 single crystals by femtosecond laser. We fabricated and characterized one-dimensional (1D) diffraction gratings with different lattice spacings of 15 and 20 lm, and with a sub-modulation of the period introduced in the later. The optical and electronic microscopy characterization and filling factor analysis of these diffraction gratings are reported. We also show that the roughness generated on the grooves by the ablation process can be impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These techniques have been successfully used for the precise surface microstructuring of crystals, thus enabling the fabrication of photonic devices. For instance, the integration of diffractive patterns (relief gratings) for beam‐shaping applications has been explored in laser and nonlinear crystals. Concerning the inscription of optical waveguides in crystals by ultrafast ablation, two approaches have been demonstrated.…”
Section: Fundamentals On Microprocessing Of Crystals With Femtosecondmentioning
confidence: 99%
“…These techniques have been successfully used for the precise surface microstructuring of crystals, thus enabling the fabrication of photonic devices. For instance, the integration of diffractive patterns (relief gratings) for beam‐shaping applications has been explored in laser and nonlinear crystals. Concerning the inscription of optical waveguides in crystals by ultrafast ablation, two approaches have been demonstrated.…”
Section: Fundamentals On Microprocessing Of Crystals With Femtosecondmentioning
confidence: 99%
“…Structuring of RTP has been demonstrated using femtosecond laser ablation [11] and wet chemical etching [12]. Reactive ion etching (RIE) is a commonly used method for etching materials in the semiconductor industry [13], however there is a lack of literature on the plasma-based micromachining of RTP and to date there haven't been any demonstrations of channel waveguide structures in RTP.…”
Section: A Choudhary 1 J Cugat 2 K Pradeesh 1 R Solé 2 F Díazmentioning
confidence: 99%
“…The sample was moved following straight lines parallel to the b crystallographic axis and all across the surface, at constant scanning speeds of 75-130 μm s −1 , avoiding the iterative passes along the same line, depending on the depth and width of the features desired to write on the surface of RTP. 18 For those scanning speeds and the focusing conditions used, the number of pulses contributing to the ablation of a point within the sample surface was 40-55, thus the peak fluence used was well above the threshold fluence.…”
Section: Ultrafast Laser Ablationmentioning
confidence: 99%
“…12 These microstructured nonlinear optical materials could provide simultaneous control over the intensity, wavelength and spatial distribution of the generated frequency. 13 Up to now, a few studies have been devoted to investigate these effects in nonlinear optical materials such as KH 2 PO 4 (KDP), 12 LiNbO 3 , 14 β-BaB 2 O 4 , 15,16 LiTaO 3 , 17 and more recently RbTiOPO 4 (RTP) 18 micro-structured by ultrafast laser ablation. In such integrated self-diffracting nonlinear crystals, it has been reported that multiple non-collinear second harmonic beams and controlled non-collinear fundamental laser beam propagation can be achieved without the requirement of additional elements such as external diffraction gratings or beam splitters.…”
Section: Introductionmentioning
confidence: 99%